Development and application of an indirect ELISA for the detection of antibody to porcine circovirus 4 in pigs. Issue 6 (11th August 2021) - Lian, Zhengmin; Liu, Jinbiao; Liu, Panrao; Zhu, Zhenbang; Yao, Xiaohui; Yuan, Lili; Hu, Danhe; Jiang, Yan; Chen, Changhai; Chen, Nanhua; Li, Xiangdong
Abstract: Porcine circovirus type 4 (PCV4) was first reported in 2019 in China. So far, the viral DNA was detected from both healthy and diseased pigs in China and South Korea by using molecular techniques including PCR and real‐time PCR. In contrast, a serological survey regarding the presence of PCV4 antibodies in the pig population was seldomly reported. In the present study, we describe the development of an indirect enzyme‐linked immunosorbent assay (ELISA) based on capsid protein for the detection of PCV4 antibodies in swine sera. After validating the specificity and sensitivity, the ELISA was used in a retrospective serological survey for PCV4 antibodies in pig sera from Jiangsu Province of China. Note that 3.44% of analyzed samples collected between 2018 and 2021 were tested positive for PCV4 antibodies. However, PCV4 genome was absent in all ELISA‐positive serum samples. Therefore, the dynamic of viremia and antibody response to PCV4 infection in pigs warrant further investigation.